An efficient and automated method to generate complex blade geometries for numerical analysis. (January 2019) - Delgado-Gutiérrez, Arturo; Cárdenas, Diego; Probst, Oliver
Abstract: This paper presents an efficient and automated algorithm for the generation of straight and curved blades, as used in horizontal- and vertical-axis wind turbines. A single B-spline surface with both structural and aerodynamic zones is constructed, based on Non-Uniform B-splines Functions. The overall process of the approximation of both 2D blade airfoils and 3D blade surfaces is presented. The main algorithm is designed to construct a detailed B-spline surface, minimizing the segmentation data of the blade and the number of control points needed. A comparison between uniform and non-uniform B-splines blades is conducted using strain energy analysis. Additionally, the Double Reflection Method is implemented as a Rotation Minimizing Frame for a robust transformation of a 3D straight blade into a curved blade, following an arbitrary 3D pole curve. The final output of the main algorithm is a low-resolution control mesh that can regenerate a high-resolution 3D curved NURBS blade. The novel method is designed as a pre-step for numerical analysis, such as classical Finite Element Method and Isogeometric Analysis.